Compiling Information-Flow Security to Minimal Trusted Computing Bases - Fournet, Cédric; Planu, Jeremy (To appear in the proceedings of Programming Languages and Systems, 20th European Symposium on Programming, ESOP 2011., 2011)
Information-flow policies can express strong security requirements for programs run by distributed parties with different levels of trust. However, this security is hard to preserve as programs get compiled to distributed systems with (potentially) compromised machines. For instance, many programs involve computations too sensitive to be trusted to any of those machines. Also, many programs are not perfectly secure (non-interferent); as they selectively endorse and declassify information, their relative security becomes harder to preserve. We develop a secure compiler for distributed information flows. To minimize trust assumptions, we rely on cryptographic protection, and we exploit hardware and software mechanisms available on modern architectures, such as secure boots, trusted platform modules, and remote attestation. We present a security model for these mechanisms in an imperative language with dynamic code loading. We define program transformations to generate trusted virtual hosts and to run them on untrusted machines. We obtain confidentiality and integrity theorems under realistic assumptions, showing that the compiled distributed system is at least as secure as the source program.